Evaluation of panoramic digital images using Panoptiq for frozen section diagnosis - Dinesh Pradhan; Sara E Monaco; Anil V Parwani; Ishtiaque Ahmed; Jon Duboy; Liron Pantanowitz (Elsevier, 2016)
Introduction: Whole slide imaging (WSI) permits intraoperative consultations (frozen sections) to be performed remotely. However, WSI files are large and can be problematic if there are tissue artifacts (e.g., tissue folds) or when slides are scanned without multiplanes (Z-stacks) to permit focusing. The Panoptiq dynamic imaging system allows users to create their own digital files that combine low power panoramic digital images with regions of interest that can be imaged using high power Z-stacks. The aim of this study was to determine the utility of the Panoptiq dynamic imaging system for frozen section telepathology. Materials and Methods: Twenty archival randomly selected genitourinary surgical pathology frozen sectional cases were evaluated using conventional light microscopy (glass slides), panoramic images, and whole slide images. To create panoramic images glass slides were digitized using a Prosilica GT camera (model GT1920C, Allied Vision Technologies) attached to an Olympus B × 45 microscope and Dell Precision Tower 810 computer (Dell). Panoptiq 3 version 3.1.2 software was used for image acquisition and Panoptiq View version 3.1.2 to view images (ViewsIQ, Richmond, BC, Canada). Image acquisition using Panoptiq software involved a pathology resident, who manually created digital maps (×4 objective) and then selected representative regions of interest to generate Z-stacks at higher magnification (×40 objective). Whole slide images were generated using an Aperio XT Scanscope (Leica) and viewed using ImageScope Software (Aperio ePathology, Leica). Three pathologists were asked to render diagnoses and rate image quality (1-10) and their diagnostic confidence (1-10) for each modality. Results: The diagnostic concordance with glass slides was 98.3% for panoramic images and 100% for WSI. Panoptiq images were comparable to the glass slide viewing experience in terms of image quality and diagnostic confidence. Complaints regarding WSI included poor focus near tissue folds and air bubbles. Panoptiq permitted fine focusing of tissue folds and air bubbles. Issues with panoramic images included difficulty interpreting low-resolution ×4 image maps and the presence of tiling artifacts. In some cases, Z-stacked areas of Panoptiq images were limited or not representative of diagnostic regions. The image file size of Panoptiq was more than 14 times smaller than that of WSI files. Conclusions: The Panoptiq imaging system is a novel tool that can be used for frozen section telepathology. Panoramic digital images were easy to generate and navigate, of relatively small file size, and offered a mechanism to overcome focusing problems commonly encountered with WSI of frozen sections. However, the acquisition of representative Panoptiq images was operator dependent with the individual creating files that may impact the final diagnosis.